HEMORHEOLOGY INDEX CHANGES IN A RAT ACUTE BLOOD STASIS MODEL: A SYSTEMATIC REVIEW AND META-ANALYSIS - Zhang, Jun-Xiu; Feng, Yu; Zhang, Yin; Liu, Yi; Li, Shao-Dan; Yang, Ming-Hui (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Blood stasis has received increasing attention in research related to traditional Chinese medicine (TCM)and integrative Chinese and Western medicine. More than 90% of research studies use hemorheology indexes toevaluate the establishment of animal blood stasis models rather than pathological methods, as hemorheology indexevaluations of blood stasis were short of the consolidated standard. The aim of this study was to evaluate the accuracyof hemorheology indexes in rat models of acute blood stasis (ABS) based on studies in which the ABS model had beenconfirmed by pathological methods.Materials and Methods: We searched the Chinese National Knowledge Infrastructure database (CNKI), ChineseMedical Journal Database (CMJD), Chinese Biology Medicine disc (CBM), Wanfang database, and PubMed for studiesof rat blood stasis models; the search identified 18 studies of rat ABS models induced by subcutaneous injection ofepinephrine combined with an ice bath. Each included study received a modified Collaborative Approach toMeta-Analysis and Review of Animal Data from Experimental Studies (CAMARADES) score list and methodologicalquality assessment, then data related to whole blood viscosity, plasma viscosity, platelet aggregation rate, erythrocyteaggregation index, and fibrinogen concentration were extracted. Extracted data were analyzed using Revman 5.3;heterogeneity was tested using Egger's test.Results: A total of 343 studies of rat blood stasis were reviewed. Eighteen studies were included in this meta-analysis;the mean CAMARADES score was 3.5. The rat ABS model revealed a significant increase in whole blood viscosity(medium shear rate), whole blood viscosity (high shear rate), plasma viscosity, platelet aggregation rate, erythrocyteaggregation index, and fibrinogen concentration compared to controls, with weighted mean differences (WMD) of 2.42mPa/s (95% confidence interval (CI) = 1.73 - 3.10); 1.76 mPa/s (95% CI = 1.28 - 2.24); 0.39 mPa/s (95% CI = 0.24 -0.55); 13.66% (95% CI = 9.78 - 17.55); 0.84 (95% CI = 0.53 - 1.16); and 1.22 g/L (95% CI = 0.76 - 1.67), respectively.Subgroup analysis showed that whole blood viscosity, plasma viscosity, and the platelet aggregation rate test methodswere more sensitive when measured at 0-24 h than at 24-72 h after induction of blood stasis.Conclusions: Rat blood stasis studies have incomplete experimental design and quality controls, and thus need anintegrated improvement. Meta-analysis of included studies indicated that the unified hemorheology index of wholeblood viscosity (medium and high shear rate), platelet aggregation rate, erythrocyte aggregation rate, and fibrinogenconcentration might be used for assessment of rat ABS models independent of pathology methods.